Edukasi Kesehatan dengan Model SECI Berbasis Augmanted Reality Terhadap Self-Care Management dan Kepatuhan Cairan pada Pasien Gagal Ginjal Kronis dengan Hemodialisis - Jamini, Theresia; Chrismilasari, Lucia Andi; Negara, Candra Kusuma; Prawira, Ricky (Journal of Telenursing (JOTING), 2025)
This study aims to analyze the effect of health education using the SECI model based on Augmented Reality (AR) on self-care management and fluid adherence in patients with chronic kidney disease undergoing hemodialysis. The method was a quasi-experimental study with a pretest-posttest approach and a control group design. The results showed a significant increase in self-care management and fluid adherence scores in the intervention group compared to the control group (p < 0.05). In conclusion, education based on the SECI model and Augmented Reality has been proven effective in improving self-management skills and fluid adherence in hemodialysis patients and positively impacting their overall quality of life.   Keywords: Augmented Reality, Health Education, Chronic Kidney Disease, Hemodialysis, Fluid Adherence, SECI Model, Self-Care Management